ANALISIS SOAL UJIAN SEMESTER OLEH GURU SENI BUDAYA DI KELAS X SMK NEGERI 2 PARIAMAN - Sari, Welly Agita; Sudarman, Yos; Marzam, Marzam (SENDRATASIK UNP, 2019)
AbstractÂ This study aims to describe the implementation of analysis of examination questions by the cultural arts teachers at Class X of Accounting Department in SMK Negeri 2 Pariaman. This type of study was qualitative research with using descriptive analysis method. The instrument of the study was the researcher and it was assisted by interview note, observation note, and documentation files. The researcher was involved in the research as a participant observer. The types of data were primary and secondary with qualitative data analysis techniques that described the problem. The result of this study indicates that the analysis of examination questions of cultural art (music) done by the teachers of SMK Negeri 2 Pariaman, which have been tested on the final exam in odd semester 2018/2019, shows the results of the existence of categories of questions that are easy, medium and difficult, based on the results of examination of students correct answers which have been recapitulated and summarized. there are six items whose material are not related to the subject, the description of questions are too broad and the questions that the teachers have never been explained in the Indonesian traditional music insight material, then the questions can be removed, replaced or corrected. The results of the analysis of questionsÂ Keywords: semester exam analysis, cultural art teacher